Evaluation of the ICT Impact on the Level of Women's Participation in the Online Market of Kazakhstan (Journal of Economic Research & Business Administration, 2022)
The aim of this study is to assess the impact of information and communication technologies (ICT)on the level of women participation in the online market in Kazakhstan before and after the COVID-19pandemic. The studies of existing concepts and economic models, domestic and foreign literary sourcesare based on the analysis of gender differences in the online sector. The data sources were primaryin-depth semi-structured interviews with respondents and a survey among 300 women, as well as secondarydata from the Bureau of National Statistics of the Republic of Kazakhstan for 2015-2020. In thisscientific study, the authors propose a methodological toolkit that includes two stages of analysis: assessmentof the level of ICT development in terms of gender for 2015-2020; quantitative assessment ofthe state and level of development of the online market in Kazakhstan. The research revealed the mostpopular marketplaces among women in Kazakhstan (Kaspi, Instagram, Wildberries, Flip, Aliexpress). Thestudy showed that the COVID-19 pandemic affected the number of online purchases and their structure,as well as the digitalization processes lead to a decrease in the specialization of women in home employmentand an increase in their level of participation. The research results can be used in the developmentof state policy for the development of women’s entrepreneurship.Key words: gender, gender economy, digitalization, ICT, online market.